Conceptual Рrovisions of Budget Federalism in the Unitary State Ukraine - Stolyarov, V.; Shinkaryuk, O.; Stolyarova, V. (Економічний вісник Донбасу, 2019)
The article defines the initial conceptual provisions of budget federalism in interaction with budgetary centralism in the order of the problem statement. The main ideas and plans of pilot project «State regulation of regional human development in the administrative region» (on the example of Khmelnitsky region) are revealed. The rights and responsibilities (main powers) of the regional state administrations and the regional councils in regulating the volume and structure of local budgets for financing the components of the Regional Human Development Index are considered. The financial self-sufficiency of regional and local authorities, local governments and united territorial communities is regulated by expenditure powers within the limits of fiscal revenues to local budgets. The ratios of budget funds of local and state levels in the Consolidated Budget of Ukraine, which are built on the basis of harmonious proportions of the «Golden Intersection», are considered. It is proposed that direct budget transfers should be carried out in accordance with the norms of financial provision of social standards for human development. Budgetary federalism in a unitary state is to regulate such scales of the financial self-sufficiency of regional authorities and local governments to assess and forecast the sources and volumes of local finances on the basis of budget and fiscal decentralization of revenues, which are determined based on expenditure powers in socio-economic development.